C. elegans as an Animal Model to Study the Intersection of DNA Repair, Aging and Neurodegeneration - Naranjo-Galindo, Francisco José; Ai, Ruixue; Fang, Evandro Fei; Nilsen, Hilde Loge; SenGupta, Tanima (Frontiers in Aging, 2022)
Since its introduction as a genetic model organism, Caenorhabditis elegans has yielded insights into the causes of aging. In addition, it has provided a molecular understanding of mechanisms of neurodegeneration, one of the devastating effects of aging. However, C. elegans has been less popular as an animal model to investigate DNA repair and genomic instability, which is a major hallmark of aging and also a cause of many rare neurological disorders. This article provides an overview of DNA repair pathways in C. elegans and the impact of DNA repair on aging hallmarks, such as mitochondrial dysfunction, telomere maintenance, and autophagy. In addition, we discuss how the combination of biological characteristics, new technical tools, and the potential of following precise phenotypic assays through a natural life-course make C. elegans an ideal model organism to study how DNA repair impact neurodegeneration in models of common age-related neurodegenerative diseases.